2019
DOI: 10.3390/w11081610
|View full text |Cite
|
Sign up to set email alerts
|

First Steps into an Integrated Karst Aquifer Vulnerability Approach (IKAV). Intrinsic Groundwater Vulnerability Analysis of the Yucatan Karst, Mexico

Abstract: Karst groundwater vulnerability maps are important tools for the development of groundwater management and protection strategies. However, current methodologies do not always match regional characteristics and parameter adaptations are necessary. In addition, other important processes such as dilution and aquifer residence time are not included in vulnerability analysis for the complications of evaluating two or more criteria simultaneously. The integrated karst aquifer vulnerability approach (IKAV) project ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, current methodologies created by the COST Action 620 approach do not always apply well to regional characteristics and parameter adaption are necessary (Moreno Gómez et al, 2018). Studies conducted by various authors (Souza, 2020;Valcarce et al, 2020;Moreno Gómez et al, 2019;Gainza et al, 2019;Moreno Gómez et al, 2018;Aguilar et al, 2016) in South American and Caribbean countries demonstrate the need to adapt methodologies that are based on European conditions.…”
Section: First Steps To Understand Intrinsic Vulnerability To Contami...mentioning
confidence: 99%
“…However, current methodologies created by the COST Action 620 approach do not always apply well to regional characteristics and parameter adaption are necessary (Moreno Gómez et al, 2018). Studies conducted by various authors (Souza, 2020;Valcarce et al, 2020;Moreno Gómez et al, 2019;Gainza et al, 2019;Moreno Gómez et al, 2018;Aguilar et al, 2016) in South American and Caribbean countries demonstrate the need to adapt methodologies that are based on European conditions.…”
Section: First Steps To Understand Intrinsic Vulnerability To Contami...mentioning
confidence: 99%
“…Doline density is variable and commonly used in models to assess aquifer vulnerability (Crawford and Veni, 1986;Ray et al, 1993;Doerfliger et al, 1999;Kochanov and Reese, 2003;Arthur et al, 2007;Biondić et al, 2021). It has been shown that high dolines density areas and strong fissuring corresponds to the areas with high and very high aquifer vulnerability (Moreno-Gómez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…That methods were applied in several catchments worldwide and, because of the specific characteristics of some karst areas, some of the methods could be applied without modification of the parameters [28,29]; whilst others had to have some parameters modified [30][31][32][33][34]. For some areas, a comparative analysis of the use of several of the most common methods of intrinsic vulnerability mapping has been conducted [35,36].…”
Section: Introductionmentioning
confidence: 99%